2004
DOI: 10.1364/opex.12.001643
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral imaging using compact compound optics

Abstract: A very thin image capturing system called TOMBO (thin observation module by bound optics) is developed with compound-eye imaging and digital post-processing. As an application of TOMBO, a multispectral imaging system is proposed. With a specific arrangement of the optical system, spatial points can be observed by multiple photodetectors simultaneously. A filter array inserted in front of the image sensor enables observation of the spectrum of the target. The captured image is reconstructed by a modified pixel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 6 publications
0
62
0
Order By: Relevance
“…A new approach to high sensitivity imaging builds upon the standard Bayer mosaic by using panchromatic pixels [4] that collect a significantly larger proportion of incident radiation. Color filter arrays (CFAs) with more than three colors have been proposed to capture multispectral images [5], [6].…”
mentioning
confidence: 99%
“…A new approach to high sensitivity imaging builds upon the standard Bayer mosaic by using panchromatic pixels [4] that collect a significantly larger proportion of incident radiation. Color filter arrays (CFAs) with more than three colors have been proposed to capture multispectral images [5], [6].…”
mentioning
confidence: 99%
“…This first MAFC implementation of which we are aware is the Fourier transform spectrometer approach by Hirai et al 58 Surprisingly, it was not until 2004 that we found an implementation like that shown in Fig. 8a, by Shogenji et al, 109 after which we find other research groups following the same approach. 110,111 This layout uses an array of lenses coregistered to an array of spectral filters, with the entire set coupled to a monolithic detector array.…”
Section: Multiaperture Filtered Camera (Mafc 1994)mentioning
confidence: 93%
“…Multi-spectral imaging [1,2] is an important technology to realize accurate spectral separation and obtain image information of different frequency bands. Combined with digital image processing technology, it can be used in many areas such as high-precision color reconstruction [3][4][5] , biomedical imaging, [6][7][8][9] and so on.…”
Section: Introductionmentioning
confidence: 99%